Dual anti‐inflammatory and anti‐parasitic action of topical ivermectin 1% in papulopustular rosacea. (29th August 2017) - Schaller, M.; Gonser, L.; Belge, K.; Braunsdorf, C.; Nordin, R.; Scheu, A.; Borelli, C.
Abstract: Background: Recently, therapy of rosacea with inflammatory lesions (papulopustular) has improved substantially with the approval of topical ivermectin 1% cream. It is assumed to have a dual mode of action with anti‐inflammatory capacities and anti‐parasitic effects against Demodex, which however has not yet been demonstrated in vivo . Aim: To find scientific rationale for the dual anti‐inflammatory and anti‐parasitic mode of action of topical ivermectin 1% cream in patients with rosacea. Methods: A monocentric pilot study was performed including 20 caucasion patients with moderate to severe rosacea, as assessed by investigator global assessment (IGA score ≥3) and a Demodex density ≥15/cm 2 . Patients were treated with topical ivermectin 1% cream once daily (Soolantra ® ) for ≥12 weeks. The density of Demodex mites was assessed with skin surface biopsies. Expression of inflammatory and immune markers was evaluated with RT‐PCR and by immunofluorescence staining. Results: The mean density of mites was significantly decreased at week 6 and week 12 ( P < 0.001). The gene expression levels of IL‐8, LL‐37, HBD3, TLR4 and TNF‐ α were downregulated at both time points. Reductions in gene expression were significant for LL‐37, HBD3 and TNF‐ α at both follow‐up time points and at week 12 for TLR4 (all P < 0.05). Reduced LL‐37 expression ( P < 0.05) and IL‐8 expression were confirmed on the protein level by immunofluorescence staining. All patients improved clinically, and 16 of 20 patients reached therapeutic success defined as IGA score ≤1. Conclusion: Topical ivermectin 1% cream acts by a dual, anti‐inflammatory and anti‐parasitic mode of action against rosacea by killing Demodex spp. in vivo, in addition to significantly improving clinical signs and symptoms in the skin.